2022
DOI: 10.3389/fneur.2022.867603
|View full text |Cite
|
Sign up to set email alerts
|

Automated Pupillometry for Prediction of Electroencephalographic Reactivity in Critically Ill Patients: A Prospective Cohort Study

Abstract: BackgroundElectroencephalography (EEG) is widely used to monitor critically ill patients. However, EEG interpretation requires the presence of an experienced neurophysiologist and is time-consuming. Aim of this study was to evaluate whether parameters derived from an automated pupillometer (AP) might help to assess the degree of cerebral dysfunction in critically ill patients.MethodsProspective study conducted in the Department of Intensive Care of Erasme University Hospital in Brussels, Belgium. Pupillary ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In a cohort of 100 mixed medical-surgical patients on mechanical ventilation, reduced PLR and constriction velocity at day 3 were independently associated with the occurrence of delirium [ 45 ]. A large study on 214 critically ill patients, including 21% diagnosed with sepsis, confirmed the high accuracy of low DV in detecting an unreactive electroencephalography in non-anoxic critically ill patients [ 46 ]. Contrary to this, a previous study of 92 septic and non-septic patients did not show any correlations between NPi and CA [ 24 ].…”
Section: Discussionmentioning
confidence: 95%
“…In a cohort of 100 mixed medical-surgical patients on mechanical ventilation, reduced PLR and constriction velocity at day 3 were independently associated with the occurrence of delirium [ 45 ]. A large study on 214 critically ill patients, including 21% diagnosed with sepsis, confirmed the high accuracy of low DV in detecting an unreactive electroencephalography in non-anoxic critically ill patients [ 46 ]. Contrary to this, a previous study of 92 septic and non-septic patients did not show any correlations between NPi and CA [ 24 ].…”
Section: Discussionmentioning
confidence: 95%
“…Another study also conducted by Godau revealed the potential of the NPi to assess treatment responses of NCSE [45]. In addition to the NPi, decreased dilation velocity (DV) was also discovered to have association with unreactive electroencephalography (EEG) signals, which is a possible utility in patients with seizure or critical illness [77].…”
Section: Non-convulsive Status Epilepticusmentioning
confidence: 99%
“…Moreover, lower %CH and CV in the early stages of intensive care unit (ICU) care were associated with the development of delirium irrespective of the baseline severity, analgesia, and sedation dose in sedated, mechanically ventilated ICU patients without brain injuries [35]. A prospective observational study based on ICU patients reported that a lower DV was independently related to unreactive EEG findings, indicating no EEG change in response to external stimuli in patients with brain injuries, such as stroke, traumatic brain injury, infection, and other medical diseases [41].…”
Section: Other Neurological Diseasesmentioning
confidence: 99%